Comparison of the Effects of Pelargonic Acid Vanillylamide and Capsaicin on Human Vanilloid Receptors. (7th September 2012) - Weiser, Thomas; Roufogalis, Basil; Chrubasik, Sigrun
Abstract : Pelargonic acid vanillylamide is like capsaicin a natural capsaicinoid from chili peppers and commonly used in food additives to create a hot sensation, even in self‐defense pepper sprays and as an alternative to capsaicin in medical products for topical treatment of pain. Although the chemical structures of both compounds are similar, preclinical data suggest that capsaicin is the more potent compound. We therefore performed voltage‐clamp recordings using cells transfected with the human vanilloid receptor TRPV1 in order to assess the responses of pelargonic acid vanillylamide and capsaicin at the receptor level. We provide evidence that at the molecular target TRPV1, the concentration‐response curves, kinetics of current activation, as well as inhibition by the competitive antagonist capsazepine were not significantly different between the two capsaicinoids. We suggest that the different effects of the two capsaicinoids observed in previous studies may rather be due to different physicochemical or pharmacokinetic properties than to different pharmacological profiles at the receptor level. Copyright © 2012 John Wiley & Sons, Ltd.